Cytotoxic and antioxidant capacity of extracts from Vaccinium meridionale Swartz (Ericaceae) in transformed leukemic cell lines - Margarita González & , Ismael Samudio, Luis Gonzalo Sequeda-Castañeda & , Crispín Celis, José Iglesias, Ludis Morales (Journal of Applied Pharmaceutical Science, 2017)
Leukemia is one of the most common malignancies in children and represents a challenge to increase life expectancy. Many studies have been conducted with the aim to find natural compounds to fight cancer; however, chemotherapy is still the most widely used treatment despite side effects as harmful to patients. In this paper the antioxidant and cytotoxic capacity of Agraz extracts (Vaccinium meridionale) in OCI AML3 and MOLT4 cells using parallel Doxorubicin was evaluated. Extractions were made using 95% methanol, methanol-distilled water (1:1), distilled water and juice. Antioxidant capacity was performed by radical cation 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid and 2,2-diphenyl-1-picryl-hydrazyl-hydrate methods, and phenols content was determined by Folin-Ciocalteu. The cytotoxic effect was evaluated on the viability of OCI AML3 and MOLT4 cells using 96-well plates for cell seeding by hemocytometer to 96h. The antioxidant capacity expressed as 50% inhibitory concentration was 1.7 ± 0.1 and 4.5 ± 0.4 mg/L for methanol extracts by radical 2,2-diphenyl-1-picryl-hydrazyl-hydrate and radical cation 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid, respectively. The phenol content was found on 104.7 ± 4.0 and 1669.7 ± 82.6 mg AG/100g for the methanol extract and lyophilized juice, respectively. A decrease in viability of OCI AML3 (24.4%) and MOLT4 (23.0%) cells was found when using Agraz methanolic extract, with Doxorubicin was 98.8 % and 85.0% respectively.
Keywords: Agraz, Vaccinium meridionale Swartz, Antioxidant capacity, Cytotoxicity, Leukemia, Colombia.